The Use of Bone Substitutes in Spine Surgery 2002
DOI: 10.1007/978-3-642-56071-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Factors stimulating bone formation

Abstract: IntroductionOsseous spinal fusion remains a cornerstone of surgical treatment of severe spinal disorders. However, the success rate is still debated and difficult to assess in the presence of metal implant material. A general failure rate of 5-30% is reported in lumbar spinal fusion [58]. Fusion capacity is influenced by numerous factors: individual biological factors, the bone graft material, and biomechanical and external factors. Predictive factors for good osseous fusion are uniformly associated with good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
0
24
0
3
Order By: Relevance
“…Allografts are considered to be highly osteoconductive [20], weakly osteoinductive and non-osteogenic [13,21]. Therefore, fusion rates in allogenic grafting can be expected to be inferior to that of autologous bones.…”
Section: Petr Suchomel Pavel Barsa Pavel Buchvald Adam Svobodnik Eva mentioning
confidence: 99%
“…Allografts are considered to be highly osteoconductive [20], weakly osteoinductive and non-osteogenic [13,21]. Therefore, fusion rates in allogenic grafting can be expected to be inferior to that of autologous bones.…”
Section: Petr Suchomel Pavel Barsa Pavel Buchvald Adam Svobodnik Eva mentioning
confidence: 99%
“…Since that time, several studies have been conducted with PEMF with differing results, 49,50 but all favorable to the effect of PEMF. In animal models, increased mineral bone density, 51 increased bone stiffness, 22,52 and more rapid incorporation of bone grafts were observed with the use of PEMF, but no significant improvement was found in the final consolidation rate. 21,23 In a prospective, double-blind, randomized clinical study, Mooney 50 observed a bone consolidation rate of 92% in interbody lumbar arthrodesis surgeries with the use of PEMF versus 65% in the control group.…”
Section: Effect Of Pulsed Electromagnetic Field On the Consolidation mentioning
confidence: 97%
“…16,17 The use of autograft obtained from the site of decompression offers consolidation rates equivalent to those of iliac autografts when the arthrodesis involves one or two levels. 12,[17][18][19] Several methods are described to optimize posterior intervertebral fusion, such as electrical stimuli application, [20][21][22] the use of autologous growth factors and the use of recombinant proteins with osteoinductive potential (rhBMP). Electrical stimulation results in bone consolidation via mechanisms related to the increased activity of osteoblasts and osteocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7,8 Engineered bone tissue constructs ought to have two major roles when implanted in vivo: 1) they offer structural sustenance to neo tissues and 2) promote osteoinduction; these simple properties stimulate cell migration, differentiation, and osteogenesis that result in the formation of new bone. 9 In the recent years, biomaterial composites have turned out to be a viable substitute of metallic implants. These biomaterials offer many possibilities for vascular grafting and stents, fracture fixations, tendons attachments, and replacement of small bone defects.…”
mentioning
confidence: 99%